Impact of screening programme using the faecal immunochemical test on stage of colorectal cancer: Results from the IMPATTO study. Issue 1 (29th April 2019) - Vicentini, Massimo; Zorzi, Manuel; Bovo, Emanuela; Mancuso, Pamela; Zappa, Marco; Manneschi, Gianfranco; Mangone, Lucia; Giorgi Rossi, Paolo; ,
Abstract : To evaluate the impact of faecal immunochemical test (FIT) screening on stage distribution at diagnosis, and to estimate relative incidence rates by stage in screened at first and subsequent rounds vs . unscreened. We included all incident cases occurring in 2000–2008 in 50‐ to 71‐year‐olds residing in areas with an FIT‐screening programme. Multinomial logistic models were computed to estimate the relative risk ratio (RRR) of stages I and IV, compared to stage II + III, adjusting for age, sex, geographical area, and incidence year. Proportions were then used to estimate incidence rate ratios (IRR) by stage for screened subjects at the first and at subsequent rounds vs . unscreened subjects, applying the expected changes in overall incidence during screening phases. 11, 663 cancers were included: 5965 in not‐invited and 5, 698 in invited subjects, 3, 425 of whom attendees. Compared to not‐invited, invited subjects had RRR 2.04 (95% CI: 1.84; 2.46) of stage I and RRR 0.77 (95% CI: 0.69; 0.87) of stage IV. Differences were stronger comparing attendees vs . nonattendees. Interval cancers were more frequently stage I compared to non‐invited (RRR 1.54; 95% CI: 1.15; 2.04), but there was no difference for stage IV. IRRs in screened at first round vs . unscreened were 4.6 (95% CI: 4.2; 5.1), 1.4 (95% CI: 1.3; 1.5) and 0.7 (95% CI: 0.6; 0.9) for stages I, II + III and IV, respectively; in the following rounds the IRRs of screened vs . unscreened were 1.4 (95% CI: 1.2; 1.6), 0.8 (95% CI: 0.7; 0.9) and 0.3 (95% CI: 0.1; 0.4) for stages I, II + III and IV, respectively. FIT screening reduces the incidence of metastatic cancers by about 70% after the first round. Abstract : What's new? Screening programs are intended to reduce mortality by early diagnosis. In this study, the authors evaluated the faecal immunochemical test (FIT) for colorectal cancer. They calculated the effect of FIT screening on stage at diagnosis, and estimated the relative incidence rates by stage. Individuals who attended screening had far higher incidence of stage I cancer, and lower incidence of stage IV, than those not screened. Metastatic cancer incidence, they found, decreased by about 70% at the first round of screening.